The Increased Endogenous Sulfur Dioxide Acts as a Compensatory Mechanism for the Downregulated Endogenous Hydrogen Sulfide Pathway in the Endothelial Cell Inflammation - Zhang, Da; Wang, Xiuli; Tian, Xiaoyu; Zhang, Lulu; Yang, Guosheng; Tao, Yinghong; Liang, Chen; Li, Kun; Yu, Xiaoqi; Tang, Xinjing; Tang, Chaoshu; Zhou, Jing; et al. (Frontiers in Immunology, 2018)
Endogenous hydrogen sulfide (H2S) and sulfur dioxide (SO2) are regarded as important regulators to control endothelial cell function and protect endothelial cell against various injuries. In our present study, we aimed to investigate the effect of endogenous H2S on the SO2 generation in the endothelial cells and explore its significance in the endothelial inflammation in vitro and in vivo. The human umbilical vein endothelial cell (HUVEC) line (EA.hy926), primary HUVECs, primary rat pulmonary artery endothelial cells (RPAECs), and purified aspartate aminotransferase (AAT) protein from pig heart were used for in vitro experiments. A rat model of monocrotaline (MCT)-induced pulmonary vascular inflammation was used for in vivo experiments. We found that endogenous H2S deficiency caused by cystathionine-γ-lyase (CSE) knockdown increased endogenous SO2 level in endothelial cells and enhanced the enzymatic activity of AAT, a major SO2 synthesis enzyme, without affecting the expressions of AAT1 and AAT2. While H2S donor could reverse the CSE knockdown-induced increase in the endogenous SO2 level and AAT activity. Moreover, H2S donor directly inhibited the activity of purified AAT protein, which was reversed by a thiol reductant DTT. Mechanistically, H2S donor sulfhydrated the purified AAT1/2 protein and rescued the decrease in the sulfhydration of AAT1/2 protein in the CSE knockdown endothelial cells. Furthermore, an AAT inhibitor l-aspartate-β-hydroxamate (HDX), which blocked the upregulation of endogenous SO2/AAT generation induced by CSE knockdown, aggravated CSE knockdown-activated nuclear factor-κB pathway in the endothelial cells and its downstream inflammatory factors including ICAM-1, TNF-α, and IL-6. In in vivo experiment, H2S donor restored the deficiency of endogenous H2S production induced by MCT, and reversed the upregulation of endogenous SO2/AAT pathway via sulfhydrating AAT1 and AAT2. In accordance with the results of the in vitro experiment, HDX exacerbated the pulmonary vascular inflammation induced by the broken endogenous H2S production in MCT-treated rat. In conclusion, for the first time, the present study showed that H2S inhibited endogenous SO2 generation by inactivating AAT via the sulfhydration of AAT1/2; and the increased endogenous SO2 generation might play a compensatory role when H2S/CSE pathway was downregulated, thereby exerting protective effects in endothelial inflammatory responses in vitro and in vivo.